2008
DOI: 10.1007/bf03349258
|View full text |Cite
|
Sign up to set email alerts
|

Severe vitamin D deficiency in the institutionalized elderly

Abstract: Severe vitamin D deficiency has been found to be prevalent in institutionalized elderly persons in several countries. The aim of the present work was to assess the vitamin D status of institutionalized elderly and compare it to that of community-living independent elderly in southern Greece during summer. Serum 25-hydroxyvitamin D [25(OH)D] and plasma PTH were measured in 58 (aged 68-103 yr, median 83.5) elderly inmates of a nursing home (IE) in the town of Kalamata (latitude N 37 degrees ) and in 48 (aged 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
2
9
0
2
Order By: Relevance
“…With a mean 25(OH)D 3 level of 39.9 nmol/L in the winter and 44.9 nmol/L in the summer, another study of elderly patients in long-term care facilities found that 18% of patients had severe vitamin D deficiency (defined as o25 nmol/L of 25(OH)D 3 ) in some seasons (usually late winter and spring) but at least 9% remained severely deficient even in summer [14]. Another recent study demonstrated severe vitamin D deficiency in many nursing home residents with a mean 25(OH)D 3 value of 19.0 nmol/L even in the summer compared to non-institutionalized seniors dwelling in the community who were found to have a mean 25(OH)D 3 level of 67.6nmol/L [3]. Furthermore, the risk of community dwelling seniors needing admission to a longterm nursing home facility is significantly increased with low vitamin D status [15].…”
Section: Vitamin D Status In Institutionalized Seniorsmentioning
confidence: 93%
See 2 more Smart Citations
“…With a mean 25(OH)D 3 level of 39.9 nmol/L in the winter and 44.9 nmol/L in the summer, another study of elderly patients in long-term care facilities found that 18% of patients had severe vitamin D deficiency (defined as o25 nmol/L of 25(OH)D 3 ) in some seasons (usually late winter and spring) but at least 9% remained severely deficient even in summer [14]. Another recent study demonstrated severe vitamin D deficiency in many nursing home residents with a mean 25(OH)D 3 value of 19.0 nmol/L even in the summer compared to non-institutionalized seniors dwelling in the community who were found to have a mean 25(OH)D 3 level of 67.6nmol/L [3]. Furthermore, the risk of community dwelling seniors needing admission to a longterm nursing home facility is significantly increased with low vitamin D status [15].…”
Section: Vitamin D Status In Institutionalized Seniorsmentioning
confidence: 93%
“…In response to ultraviolet-B radiation from sunlight, vitamin D is obtained primarily from conversion of cutaneous 7-dehydrocholesterol to cholecalciferol (vitamin D 3 ), but can also be acquired from a limited number of primary foods, fortified foodstuffs, and through supplementation [1]. Vitamin D 3 is hydroxylated in the liver to 25(OH)D 3 -the main circulating metabolite which is used as the predominant biomarker of clinical vitamin D status.…”
Section: Biological Role Of Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that living situation (i.e. living alone vs living with family vs living in an aged care facility) can influence an individual's nutritional status . The importance of optimising nutrition in the management of COPD has been recognised globally and recommendations to this effect are seen in the practice guidelines of every major respiratory society…”
Section: Introductionmentioning
confidence: 99%
“…living alone vs living with family vs living in an aged care facility) can influence an individual's nutritional status. 19,20 The importance of optimising nutrition in the management of COPD has been recognised globally and recommendations to this effect are seen in the practice guidelines of every major respiratory society. 1,21 Numerous studies have shown that MD are common in subjects with COPD, in contrast, however, interventions aimed at addressing these deficiencies have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%